PENERAPAN METODE EKLEKTIK DALAM PEMBELAJARAN BAHASA ARAB UNTUK MENINGKATKAN MOTIVASI BELAJAR DI SMP ISLAM AL-BAYYINAH MAKASSAR - Sofiana; Qahar Zainal, Abdul; Nengsih, Ratika; Beddu Malla, Agussalim; Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the motivation to learn Arabic of seventh-grade students of Al-Bayyinah Islamic Junior High School Makassar through the application of eclectic methods. The background of this study is the low motivation of students to learn, indicated by the lack of activeness, interest, and enthusiasm in participating in Arabic learning which is still dominated by conventional methods. This study uses a Classroom Action Research (CAR) approach with the Kemmis and McTaggart model consisting of two cycles, namely planning, action implementation, observation, and reflection. The subjects of the study were 35 seventh-grade students of Al-Bayyinah Islamic Junior High School Makassar. Data collection techniques include observation, learning motivation questionnaires, documentation, and field notes. Data analysis was carried out descriptively quantitatively and qualitatively through the calculation of scores, percentages, and interpretation of observation results. The results showed that the application of eclectic methods was able to increase students' learning motivation gradually. In the pre-cycle stage, as many as 23 students (65.71%) were in the low motivation category, 10 students (28.57%) were in the sufficient category, and 2 students (5.71%) were in the high category. After the action in Cycle I, learning motivation increased to 5 students (14.29%) in the very high category, 10 students (28.57%) in the high category, 19 students (54.29%) in the sufficient category, and only 1 student (2.86%) in the low category. In Cycle II, there was a more significant increase, namely 12 students (34.29%) were in the very high category, 20 students (57.14%) in the high category, and 3 students (8.57%) in the sufficient category, with no more students in the low or very low categories. The observation results also showed an increase in student activity, courage to ask questions, cooperation, and participation during learning. Thus, the application of the eclectic method has proven effective in increasing the motivation to learn Arabic in grade VII students of SMP Islam Al-Bayyinah Makassar.